Individualization of training based on sprint force-velocity profiles: A conceptual framework for biomechanical and technical training recommendations - Hicks, D. S.; Drummond, C.; Williams, K. J.; Pickering, C.; van den Tillaar, R. (Strength and Conditioning Journal, 2023)
The purpose of this article is to provide practitioners with a system to categorize and individualize training prescription from sprint force-velocity (F-v) profiles to enhance performance in team and individual sport athletes. Despite F-v variables presenting key information about the underpinning mechanisms contributing to sprint performance, the overall data interpretation may be limited for the practitioner to implement applied training interventions compared with the researcher. Therefore, this article provides a conceptual framework for appropriate training prescriptions based on individual biomechanical and technical characteristics contributing to sprint performance.